PENERAPAN PENDEKATAN PROSES UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI KELAS III SDN 34 PONTIANAK KOTA - Ghofur, Abdul; Halidjah, Siti; kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to improve writing poetry skills applying process approach. The research procedure consists of planning, action, observation, and reflection. The subjects of the research were teachers and students of grade III D, which amounted to 31 consisting of 14 males and 17 females. Techniques of collecting data in the form of observation, documentation and questionnaire. Data analysis techniques by qualitative descriptive analysis used to analyze the data in the form of descriptions accompanied by simple calculations, and the presentation of data averages and percentages are then changed in the form of tables and graphs. The results showed that cycle I, the average score of 70.32 students increased in cycle II to 77.24 and increased in cycle III to 83.87 and then increased to 85.83 in the IV cycle with an increase of 14.51. Classical completeness in cycle I is 54,84% increase in cycle II become 70,42% increase in cycle III become 96,77% and become 100% in cycle IV with very high increase that is 45,16%. Based on the questionnaire obtained a total of 481 with a percentage of 87.81% (the category